Análisis biométrico de las características faciales de la población colombiana. parte II: tejidos blandos - Jones-G., Monica; Betancur-P., John Jairo; Bojanini-G., Ana Cristina (Revista Facultad de Odontología Universidad de Antioquia, 2016)
At present there are no soft tissue studies statistically valid, that show the applicability of the international standards in our population. The purpose of this study was to establish the standards of the prevalent facial morphology in Medellin, Colombia, according to sex and socioeconomical status, and to determine their difference with the foreign standards. Lateral cephalometric radiographs and two photographs (front and lateral view) were taken of 106 adults (53 women/53 men), 18 to 29 years of age, with Colombian parents and grandparents; Class I occlusion without evident crowding; good facial harmony; without medical records of orofacial secuelae; without previous orthodontics or facial orthopedics; without congenital abscence of laterals or loss of two contiguous teeth. Nineteen variables were analyzed and neither one of them showed difference according to the socioeconomical status. Sexual dimorphism, statistically significant, was found in six measurements. The Nasolabial Angle did not show any sexual dimorphism. It was found that for five variables we must only use our own standards; in four variables the international standard must be used cautiously and in the other eight variables these standards can be used with ease.